Analisis Penerapan Metode Altman Z-Score untuk Prediksi Kebangkrutan PT Kimia Farma Tahun 2019–2023 - Nur Adni Putri Chantika; Yusleli Herawati; Divianto Divianto (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to examine the potential bankruptcy of PT Kimia Farma during the 2019–2023 period by employing the Altman Z-Score method, which is widely recognized as an analytical tool for predicting corporate financial distress. The Altman Z-Score model evaluates company performance by integrating several financial ratios, thereby providing an indication of whether a company falls into a safe, gray, or bankruptcy zone. This research adopts a quantitative descriptive approach, using secondary data obtained from PT Kimia Farma’s annual financial reports covering the years 2019 to 2023. The analysis is conducted by calculating five financial ratios that comprise the Altman Z-Score model, namely working capital to total assets, retained earnings to total assets, earnings before interest and tax to total assets, market value of equity to total liabilities, and sales to total assets. The findings of this study reveal that PT Kimia Farma was consistently in the gray zone during the period of 2019–2021, suggesting that the company faced financial instability and a moderate risk of bankruptcy. However, the results further indicate that in 2022 and 2023, the company shifted into the bankruptcy zone, signaling an alarming decline in financial health and highlighting the urgent need for managerial attention. This decline reflects weaknesses in profitability, liquidity, and leverage management, which, if not addressed promptly, may threaten the company’s long-term sustainability. The results of this study are expected to provide meaningful contributions both practically and academically. For practitioners, particularly company management, the study serves as valuable input for reassessing financial strategies, strengthening internal controls, and formulating policies aimed at restoring financial stability. For academics and future researchers, the findings offer a relevant reference for studies concerning bankruptcy prediction, financial performance evaluation, and corporate risk management, especially in the context of state-owned enterprises in Indonesia.